Modeling of Fire Traits to Allot Fire Service Resources in the Most Efficient Way Possible - Yuldashev Ismoil Zhuraevich; Yangiboyev Khurshidbek Nurmuhammad o’g’li (European Journal of Life Safety and Stability (2660-9630), 2023)
The essay investigates the connections between the primary factors that influence how fires spread at various facilities that guarantee the fire safety of industrial companies and areas. To support the sufficiency of the fire service’s resources and their logical distribution, the modeling of a fire’s characteristics during its emergence and extinguishment is taken into account.